The Struggle of the people of the Julian March for freedom and self-determination = Bor'ba narodnaseleniia Iuliiskoi Krainy za svobodu i samoopredeleuie = Lutte du peuple de la Marche Julienne pour la liberté et le droit à disposer de lui-même. (Ljubljana, 1946)
Bibliotheek Camille Huysmans
Engels
Sloveens
Frans
Meerdelige publicatie
Keywords: Wereldoorlog 2; territoriale kwesties; Trieste; Venezia Giulia; Slovenië